The mixed‐bed glacial landform imprint of the North Sea Lobe in the western North Sea. Issue 6 (28th January 2019) - Roberts, David H.; Grimoldi, Elena; Callard, Louise; Evans, David J.A.; Clark, Chris D.; Stewart, Heather A.; Dove, Dayton; Saher, Margot; Ó Cofaigh, Colm; Chiverrell, Richard C.; Bateman, Mark D.; Moreton, Steven G.; et al.
Abstract: During the last glacial cycle an intriguing feature of the British‐Irish Ice Sheet was the North Sea Lobe (NSL); fed from the Firth of Forth and which flowed south and parallel to the English east coast. The controls on the formation and behaviour of the NSL have long been debated, but in the southern North Sea recent work suggests the NSL formed a dynamic, oscillating terrestrial margin operating over a deforming bed. Further north, however, little is known of the behaviour of the NSL or under what conditions it operated. This paper analyses new acoustic, sedimentary and geomorphic data in order to evaluate the glacial landsystem imprint and deglacial history of the NSL offshore from NE England. Subglacial tills (AF2/3) form a discontinuous mosaic interspersed with bedrock outcrops across the seafloor, with the partial excavation and advection of subglacial sediment during both advance and retreat producing mega‐scale glacial lineations and grounding zone wedges. The resultant 'mixed‐bed' glacial landsystem is the product of a dynamic switch from a terrestrial piedmont‐lobe margin with a net surplus of sediment to a partially erosive, quasi‐stable, marine‐terminating, ice stream lobe as the NSL withdrew northwards. Glaciomarine sediments (AF4) drape the underlying subglacial mixed‐bed imprint and point to a switch to tidewater conditions between 19.9 and 16.5 ka cal BP as the North Sea became inundated. The dominant controls on NSL recession during this period were changing ice flux through the Firth of Forth ice stream onset zone and water depths at the grounding line; the development of the mixed‐bed landsystem being a response to grounding line instability. © 2018 John Wiley & Sons, Ltd. Abstract : During the last glacial cycle the retreat and advance of the North Sea Lobe left a 'mixed‐bed' glacial landsystem imprint on the floor of the western North Sea. The production of this unusual landform assemblage represents a dynamic switch from a terrestrial piedmont‐lobe margin with a net surplus of sediment to the south, to a partially erosive/excavational, quasi‐stable, ice margin as ice withdrew northwards under glaciomarine conditions.